2011
DOI: 10.1111/j.1365-2990.2011.01184.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of distinct galectins in multiple sclerosis lesions

Abstract: This study provides a detailed analysis of galectins in MS lesions and assigns distinct galectins to different aspects of the disease. Thus, besides being known as modulators of inflammatory processes, our findings suggest additional association of distinct galectins with MS pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 60 publications
(67 reference statements)
3
58
0
1
Order By: Relevance
“…The involvement of Gal-9 in modulating the neuroinflammatory events in MS are supported by several lines of evidence. First, Gal-9 expression is increased in MS lesions (13,14). Second, the Gal-9 receptor, Tim-3, is dysregulated on T-cells isolated from the circulation of MS patients, thereby rendering the T-cells less susceptible to the immunoregulatory outcomes after Gal-9 ligation (15).…”
Section: Multiple Sclerosis (Ms)mentioning
confidence: 99%
“…The involvement of Gal-9 in modulating the neuroinflammatory events in MS are supported by several lines of evidence. First, Gal-9 expression is increased in MS lesions (13,14). Second, the Gal-9 receptor, Tim-3, is dysregulated on T-cells isolated from the circulation of MS patients, thereby rendering the T-cells less susceptible to the immunoregulatory outcomes after Gal-9 ligation (15).…”
Section: Multiple Sclerosis (Ms)mentioning
confidence: 99%
“…Gal-3 has been implicated in MS; it is expressed at high levels in active lesions around the lateral ventricles, and it modulates animal models of MS [16, 23]. Gal-3 was initially termed Mac-2 because it was identified in activated macrophages [24].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in vitro have shown that galectin-9 can induce maturation of human monocyte-derived dendritic cells [33] and enhance proinflammatory cytokine secretion [34], which have been attributable to its ability to bind the highly glycosylated T-cell immunoglobulin and mucin domain-containing protein 3 (Tim-3) [34]. While galectin-9 protein or the gene encoding galectin-9, Lgals9 , is not normally expressed at high levels within the CNS [35,36], it is increased following experimental pneumococcal meningitis [37] as well as infection with herpes simplex virus [38] or Japanese encephalitis virus [39] and is reportedly increased in the brains of multiple sclerosis patients [34,40], indicating that it becomes up-regulated during inflammatory conditions.…”
Section: Introductionmentioning
confidence: 99%